Factors affecting purchase of online music in Australia - Butcher, Luke; Marchegiani, Chris (School of Marketing, Curtin Business School, 2010)
Digital Music is purchased online by an increasing number of consumers and looks set to grow. The purpose of this research is to provide an explanation of factors influencing purchase intention of the Australian consumer of online music. Such a study will help practitioners and marketing managers of online music to better develop market strategies. This research will draw upon the theoretical underpinnings of the Value Intention Framework adapted by Chu and Lu (2007) to examine the willingness of consumers purchasing online music. This model has been previously used to identify consumers in other geographic locations, for example Taiwan, but has not been tested in the Australian context. This research will be undertaken to fulfil the gap identified through previous researchers by examining a model of online music purchase behaviour in the Australian context. The findings will identify whether the perceived value of online music is a significant factor in predicting the purchaser intention of buying online music in Australia. It will also identify whether perceived benefit and perceived sacrifice effects consumers perceived value.The results of this study will facilitate understanding of what encourages and impedes the purchase intention of consumers of online music in Australia. It will afford each player within the Digital Music Value Chain a greater understanding of how to improve the purchase intentions of online music customers in Australia.